A general equilibrium analysis of check float - James McAndrews; William Roberds (Federal Reserve Bank of Atlanta, 1997)
Households and businesses in the United States prefer to use check payment over less costly, electronic means of payment. Earlier studies have focused on check "float," that is, the time lag between receipt and clearing, as a potential explanation for the continued popularity of checks. An underlying assumption of these studies is that check float operates as a pure transfer from payee to payor. We construct a simple general equilibrium model in which payments are made by check. In general equilibrium, check float does not act as a pure transfer. If float can be priced into market transactions, then it has no effect on equilibrium allocations. If float is not priced into market transactions, then it acts as a distorting tax. Our results are consistent with the view that float is a significant factor behind the continued popularity of check payment. Our results are also consistent with recent data that indicate that the average value of float (per check) is small.
Keywords: 330; Checks; Financial services industry; Payment systems